PENGARUH BUDAYA ORGANISASI DAN ETOS KERJA TERHADAP KINERJA KARYAWAN PT. GEMILANG JAYA - Naufal Yuwantono; Drs. Widodo MM (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
Human resources have an important function in determining success when companies face the challenges of globalization. This study aims to analyze the influence of organizational culture and work ethic on the performance. The sampling technique used is simple random sampling. As many as 84 employees of PT. Gemilang Jaya. The analytical tool used is path analysis with the help of SPSS version 22. The results show simultaneously organizational culture and work ethic capable of positive and significant, partially organizational culture is able to have a positive and significant and partially work ethic can have a positive and significant.